A questão da liberação das drogas: discurso, fábula e mídia no curta animado Guerra ao Drugo - TRUCI, Fabio Barros (2017)
The purpose of this dissertation is to reflect on the process of production and placement of an animated piece of advertising that treats, as a fable, the problem of drug decriminalization. The animation short in focus here is War on Drugs, conducted by the agency AlmapBBDO and the NGO Global Commission on Drug Policy, in 2014. For this research, I used three strategies: the first was to study the discursive organization that animation develops ; the second emerges from the fabular construction of the narrative; and the third deals with the media chosen to deliver the animated short film - YouTube. Based on the above strategies, I initially approach the materialization of the tactics of criminalization and the decriminalization of drugs in the media. Next, I search the technique and processes used in the production of the piece, deconstructing the advertising campaign, scene the scene, for an evaluation of the expressive choices, as well as the strategic use of the fable in the construction of the narrative of the film. And finally, I look for possible motives for the unimportant placement on YouTube's web video platform of the short film in favor of drug release War on Drugo.